cpSRP43 is a novel chaperone specific for light-harvesting chlorophyll a,b-binding proteins - Falk, Sebastian; Sinning, Irmgard (The journal of biological chemistry, 2010)
The biosynthesis of most membrane proteins is directly coupled to membrane insertion, and therefore, molecular chaperones are not required. The light-harvesting chlorophyll a,b-binding proteins (LHCPs) present a prominent exception as they are synthesized in the cytoplasm, and after import into the chloroplast, they are targeted and inserted into the thylakoid membrane. Upon arrival in the stroma, LHCPs form a soluble transit complex with the chloroplast signal recognition particle (cpSRP) consisting of an SRP54 homolog and the unique cpSRP43 composed of three chromodomains and four ankyrin repeats. Here we describe that cpSRP43 alone prevents aggregation of LHCP by formation of a complex with nanomolar affinity, whereas cpSRP54 is not required for this chaperone activity. Other stromal chaperones like trigger factor cannot replace cpSRP43, which implies that LHCPs require a specific chaperone. Although cpSRP43 does not have an ATPase activity, it can dissolve aggregates of LHCPs similar to chaperones of the Hsp104/ClpB family. We show that the LHCP-cpSRP43 interaction is predominantly hydrophobic but strictly depends on an intact DPLG motif between the second and third transmembrane region. The cpSRP43 ankyrin repeats that provide the binding site for the DPLG motif are sufficient for the chaperone function, whereas the chromodomains are dispensable. Taken together, we define cpSRP43 as a highly specific chaperone for LHCPs in addition to its established function as a targeting factor for this family of membrane protein.